ADOLESCENT PREGNANCY WORLDWIDE: A NARRATIVE REVIEW - Yuniarini Yuniarini (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Adolescent pregnancy has become a growing concern nowadays and hence it has become imperative to look into the various causes of teenage pregnancy in order to deal with this issue carefully. Adolescent pregnancies are widely discouraged because the of health risks raised for the young mothers and babies. Adolescent pregnancies create a host of other problems like incomplete education, unemployment, poverty, social embarrassment and numerous other emotional traumas. Further, early motherhood also affects the psychological development of the child adversely. Adolescent pregnancy can also have negative social and economic effects on girls, their families and communities. Besides, bodies of teenage girls are not as developed as those of adult women in terms of childbearing, therefore, they are likely to face certain complications as well. Early childbearing increases the risks for both mothers and their newborns.Moreover, the chances of maternal death can not be ruled out. Therefore, analyzing the various causes of adolesecent pregnancy can help a great deal in addressing this issue effectively and eventually reducing the cases of adolescent pregnancies.